2021
DOI: 10.3390/su132011386
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autogenous and Stimulated Self-Healing on Durability and Mechanical Performance of UHPFRC: Validation of Tailored Test Method through Multi-Performance Healing-Induced Recovery Indices

Abstract: Chloride diffusion and penetration, and consequently chloride-induced corrosion of reinforcement, are among the most common mechanisms of deterioration of concrete structures, and, as such, the most widely and deeply investigated as well. The benefits of using Ultra-High Performance (Fiber-Reinforced) Concrete—UHP(FR)C to extend the service life of concrete structures in “chloride attack” scenarios have been addressed, mainly focusing on higher “intrinsic” durability of the aforementioned category of materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The higher the chloride content, the faster and better the crack healing with CA occurred. More recently, Cuenca et al [219] studied the effect of autogenous healing and CA as a healing agent on the chloride ingress of cracked ultra-high performance fibre-reinforced concrete (UHPFRC). Cracks with a width of 100 ± 50 μm were generated, and the cracked samples were immersed in 3% NaCl solution for 1, 3, 6 and 12 months.…”
Section: Self-healing Under Aggressive Environmental Conditionsmentioning
confidence: 99%
“…The higher the chloride content, the faster and better the crack healing with CA occurred. More recently, Cuenca et al [219] studied the effect of autogenous healing and CA as a healing agent on the chloride ingress of cracked ultra-high performance fibre-reinforced concrete (UHPFRC). Cracks with a width of 100 ± 50 μm were generated, and the cracked samples were immersed in 3% NaCl solution for 1, 3, 6 and 12 months.…”
Section: Self-healing Under Aggressive Environmental Conditionsmentioning
confidence: 99%
“…56 This is a quite severe assumption and, however, it should be noted that in the case of UHPC, as an advantage in comparison to other materials, the tendency to have narrower crack widths can potentially delay the corrosion process. Furthermore, it is worth remarking that recent studies 21,57,58 have demonstrated the delay in terms of chlorides penetration due to the autogenous self-healing properties, also favored by the presence of crystalline admixture even for quite high values of initial crack openings (up to 0.5 mm). The same self-healing capacity is able to compensate for early age cracking, for example, due to restrained shrinkage.…”
Section: Uhpc Fibers and Steel Reinforcement Corrosionmentioning
confidence: 97%
“…A similar phenomenon was observed for chloride solution at two months. The chloride binding capacity of the cement might have fostered the sealing process [22]. Upon longer exposure periods, the differences among the environments are negligible, and only at twelve months a more pronounced recovery was observed for specimens in tap water.…”
Section: Direct Tensile Testsmentioning
confidence: 99%